Ground reaction force and electromyographic activity of transfemoral amputee gait: a case series - Cerqueira, Alex Sandra Oliveira de (2019)
Made available in DSpace on 2019-09-12T16:26:13Z (GMT). No. of bitstreams: 0 Previous issue date: 2013